Biochemical markers of neurodegeneration in hereditary diffuse leucoencephalopathy with spheroids - Spitzer, Philipp; Kohl, Zacharias; Gölitz, Philipp; Coras, Roland; Blümcke, Ingmar; Brueck, Wolfgang; Dörfler, Arnd; Maihöfner, Christian (BMJ Case Reports, 2014)
Hereditary diffuse leucoencephalopathy with spheroids (HDLS) is a rare autosomal dominantly inherited disease with unknown pathophysiology. Diagnosis of neurodegenerative diseases is increasingly based on biomarkers. Although lumbar puncture is routinely performed during the diagnostic workup of HDLS, reports on alterations of neurodegeneration-specific biochemical markers have not been documented so far. We report a 35-year-old woman with clinical, radiological and neuropathological signs of HDLS. She suffered from a rapidly progressive frontal lobe syndrome. Brain MRI revealed diffuse leucoencephalopathy with predominant involvement of the periventricular white matter and corpus callosum. Although she was severely impaired and leucoencephalopathy was prominent, only cerebrospinal fluid total-? was moderately elevated. Other markers of neuronal (NSE) and astrocytic (S100B) damage were within normal range. Therefore, biochemical markers of central nervous system damage are not helpful in the diagnosis of HDL
EVALuna2:7264